Analysis of the Effect of an Open Economy on Indonesia's National Income - Rizki Yuda Musidi; Mutiara Azzahra; Lien Febrina; Eka Rindah Yani; Muhammad Tsaqifa Ifada; Nurlela Nurlela; Disya Ayu Rivtryana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the impact of various factors, such as the value of exports and the value of imports, on Indonesia's total national income. These factors are considered as independent variables, while the amount of Indonesia's national income is the dependent variable. The research methodology involves a descriptive quantitative approach and explanatory research, with a focus on the analysis of Indonesia's national income from 1993 to 2024. The required data was obtained from secondary sources such as the Central Statistics Agency, Uncomtrade , Trademap , books, and similar research-related publications. To analyze the data, multiple linear regression statistical methods were used with the help of SPSS version 27 software. The results of the analysis show that overall (F test), the factors studied have a significant influence on the amount of national income. Furthermore, partial analysis (t test) shows that the variables of Indonesia's export value and import value also have a significant influence on Indonesia's total national income.